Using the slit diffusion function to evaluate the quality of images in optical systems. (Journal of the College of Basic Education, 2023)
A variety of methods exist for evaluating the performance of optical systems, a very common principle is to have a system under test project an image of a well defined object. In early days it had been shown the advantage of a single bar. The image of an incoherently illuminated single bar (Bar spread function) will be attacked and solved for the case of aberration free circular aperture and in the presence of off-axis aberration and on- axis aberration. The evaluation of the bar spread function for the previous case was achieved by integration over the exit pupil using Gauss quadrature.